Why Do CD8+ T Cells become Indifferent to Tumors: A Dynamic Modeling Approach - Campbell, Colin; Zhang, Ranran; Haley, Jeremy S.; Liu, Xin; Loughran, Thomas; Schell, Todd; Albert, Reka; Thakar, Juilee (Frontiers in Physiology, 2011)
CD8+ T cells have the potential to influence the outcome of cancer pathogenesis, including complete tumor eradication or selection of malignant tumor escape variants. The Simian virus 40 large T-antigen oncoprotein promotes tumor formation in T-antigen transgenic mice and also provides multiple target determinants (sites) for responding CD8+ T cells in C57BL/6 (H-2b) mice. To understand the in vivo quantitative dynamics of CD8+ T cells after encountering T-antigen, we constructed a dynamic model from in vivo-generated data to simulate the interactions between T-antigen expressing cells and CD8+ T cells in distinct scenarios including immunization of wild type C57BL/6 mice and of T-antigen transgenic mice that develop various tumors. In these scenarios the model successfully reproduces the dynamics of both the T-antigen-expressing cells and antigen specific CD8+ T cell responses. The model predicts that the tolerance of the site-specific T cells is dependent on their apoptosis rates and that the net growth of CD8+ T cells is altered in transgenic mice. We experimentally validate both predictions. Our results indicate that site-specific CD8+ T cells have tissue-specific apoptosis rates affecting their tolerance to the tumor antigen. Moreover, the model highlights differences in apoptosis rates that contribute to compromised CD8+ T cell responses and tumor progression, knowledge of which is essential for development of cancer immunotherapy.